2016
DOI: 10.1093/cid/ciw516
|View full text |Cite
|
Sign up to set email alerts
|

Infrequent Clinical Assessment of Chronic Hepatitis B Patients in United States General Healthcare Settings: Table 1.

Abstract: Among 2338 chronic hepatitis B patients followed during 2006-2013 in the Chronic Hepatitis Cohort Study, 78% had ≥1 alanine aminotransferase and 37% had ≥1 hepatitis B virus DNA level assessed annually. Among cirrhotic patients, 46% never had hepatic imaging. Patients in this cohort were insufficiently monitored for disease activity and hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 12 publications
2
33
1
Order By: Relevance
“…Liver ultrasound for hepatocellular carcinoma screening was also infrequently performed, though few patients would likely have met current recommendations for screening. Similar findings have been observed in other observational studies . This may have been due to clinicians’ lack of awareness of guidelines for HBV care in pregnant HBV‐infected women.…”
Section: Discussionsupporting
confidence: 88%
“…Liver ultrasound for hepatocellular carcinoma screening was also infrequently performed, though few patients would likely have met current recommendations for screening. Similar findings have been observed in other observational studies . This may have been due to clinicians’ lack of awareness of guidelines for HBV care in pregnant HBV‐infected women.…”
Section: Discussionsupporting
confidence: 88%
“…Our data illustrate the timing of the decline in FIB4 that follows, suggesting a delayed but significant regression of liver fibrosis. In untreated patients, it has long been recognized that the fluctuating nature of chronic HBV infection necessitates careful surveillance; however, a recent study found that such surveillance is often inadequate . This may be cause for concern, as we observe that FIB4 increases in our untreated patient sample, suggesting fibrosis progression—even among the subset of patients who were not candidates for therapy based on current guidelines.…”
Section: Discussionmentioning
confidence: 72%
“…In untreated patients, it has long been recognized that the fluctuating nature of chronic HBV infection necessitates careful surveillance 27 ; however, a recent study found that such surveillance is often inadequate. 28,29 This may be cause for concern, as we observe that FIB4 increases in our untreated patient sample, suggesting fibrosis progressioneven among the subset of patients who were not candidates for therapy based on current guidelines. Because of the observational nature of our study, prospective studies are needed to further characterize which patients are at highest risk for fibrosis progression.…”
Section: Discussionmentioning
confidence: 90%
“…Although effective therapies are available for managing HIV, HBV, and HCV infections, these infections sometimes remain undiagnosed because of their often asymptomatic nature [4–6]. Public health efforts to test and link persons with HIV and viral hepatitis infections to care are of crucial importance for mitigating associated morbidity and mortality [79].…”
Section: Introductionmentioning
confidence: 99%